The Effect of Financial Performance on Profit Growth in Automotive Companies Listed on IDX - Hendra, Aldi Alma; Haninun, Haninun; Aminah, Aminah (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
Profit growth has an important role in evaluating the performance of a company, when the development of business entity profits is higher, shareholders tend to be interested in putting their investment because they believe that the company has positive prospects in the future. The purpose of this study was to examine the effect of financial performance, namely Current Ratio, Net Profit Margin, and Total Asset Turnover on profit growth in Automotive Companies. This type of research used is quantitative using secondary data from Automotive Companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2022 with a research sample of 31 samples. The analysis technique uses multiple regression analysis with the spss statistical test tool. The results of this study are that Net Profit Margin has a significant positive effect, while other factors such as Current Ratio and Total Asset Turnover do not show a significant effect. However, simultaneously Current Ratio, Net Profit Margin, and Total Asset Turnover affect profit growth.